Who to Trust? Applying Trust to Social Commerce. Issue 1 (2nd January 2019) - Sharma, Shwadhin; Menard, Philip; Mutchler, Leigh A.
ABSTRACT: Organizations have recognized the revenue potential for social commerce (purchasing products via social networks), but such transactions only comprise a small percentage of revenue. Companies have yet to determine the factors that contribute to social commerce failure. In social networking, trust is established when two parties have a history of trustworthy interactions. Acknowledging that social commerce represents a fundamentally different purchasing environment than typical business transactions, we examine the role of trust in determining consumers' decisions to engage in social commerce for their purchases. We apply trust transfer theory to the social commerce context to assess whether trust in known entities can be transferred to business transactions facilitated through a social network with unknown parties. Using a field survey, we found that trust in the Internet and trust in firms significantly influence consumers' trust and ultimately their intention to engage in social commerce. Implications for research and practice are discussed.